PEMBELAJARAN MATERI GERAK BENDA UNTUK SISWA SD DENGAN MEDIA CANVA VIDEO - Moh. Danar Hidayah; Yayat Ruhiat; Isti Rusdiyani (Jurnal Penelitian Pendidikan IPA, 2023)
Science and Technology (IPTEK) is developing rapidly and has provided many changes Science and Technology (IPTEK) is developing rapidly and has provided many changes from various fields in Indonesia. One of the changes that has occurred in the field of education is marked by the occurrence of a pandemic, where technology is now increasingly being recognized and utilized, such as learning media. Learning media is used as a supporting mediator for the learning process so that it is effective and efficient in various environmental conditions, both pandemic and non-pandemic, such as using learning media based on the Canva video software. This study aims to develop content for learning Natural Sciences (IPA) material for motion of objects based on canva video for Elementary School (SD) students. This type of research uses research and development (Research and Development) which is commonly called RND by using the research and development model from Borg and Gall (1989) there are 10 steps to implementing a development research strategy. However, researchers only carried out 3 stages, namely research and initial information gathering, planning, and developing initial product drafts. Thus this research resulted in the development of material motion material content for elementary school students using Canva video which has the potential to become a learning medium that contains material on bats, ducks and camels. In addition, canva videos display content with the narrator's facial features with attractive color designs, text, and images. Â  Â